Novel Competency Development for Occupational Health Nurses: A Study on Training Needs Assessment in Indonesia - Prasetyono, Juli Dwi; Permatasari, Henny; Setiawan, Agus; Mulyono, Sigit; Susanto, Tantut; Mansyur, Muchtaruddin (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction: The growing demand for continuous professional development (CPD) within the healthcare sector has emphasized the importance of tailored training for various professional roles, including those of occupational health nurses. In Indonesia, there remains a need to better understand the specific job functions and development needs of nurses working in occupational health settings to ensure effective practice and optimal patient outcomes. Objective: This study was conducted to map out the roles performed by occupational health nurses in Indonesia and to identify key areas where additional training is most needed. Method: A descriptive cross-sectional approach was employed, involving 43 occupational health nurses selected via simple random sampling. Data were gathered using the validated Indonesian adaptation of the Hennessy-Hicks Training Needs Analysis Questionnaire, which evaluates competencies across five domains: research and audit, communication and teamwork, clinical practice, administrative tasks, and leadership or supervisory roles. To determine areas of significant training need, independent t-tests were performed for each questionnaire item. Results: The analysis revealed considerable training requirements in 38 of the assessed items. The domain most urgently requiring development was research and audit, which had the highest mean score (2.07). This was followed by clinical functions and management (both 1.65), mental health and resilience-related skills (1.32), collaboration and communication (1.22), and administrative functions (0.58). Conclusion: The findings point to a clear need for competency-based training initiatives, with particular emphasis on strengthening research and audit capabilities among occupational health nurses. Healthcare institutions in Indonesia are advised to implement structured educational programs alongside continuous evaluation systems to foster professional advancement and maintain high standards of care.